2021
DOI: 10.1002/adsc.202100206
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Diastereoselective Synthesis of (Z)‐Conjugated Enynyl Homoallylic Alcohols

Abstract: The diastereoselective synthesis of antihomoallylic alcohols bearing conjugated (Z)-enynes through a palladium-catalyzed three-component reaction is described. This reaction features a broad substrate scope, good functional group compatibility, and high levels of (Z)-alkene stereocontrol. In this reaction, Pd(0) functions as a catalyst in two fundamental steps of the tandem sequence: 1) the generation of a borylated π-allylpalladium species from bifunctional conjunctive reagents, inducing umpolung allylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…A recent example of complex multicomponent synthesis was described by Horino and co-workers [ 188 ]. In the reaction ( Scheme 12 ), the authors observed high levels of ( Z )-alkene stereocontrol.…”
Section: Catalysis In Stereoselective Mcrsmentioning
confidence: 99%
“…A recent example of complex multicomponent synthesis was described by Horino and co-workers [ 188 ]. In the reaction ( Scheme 12 ), the authors observed high levels of ( Z )-alkene stereocontrol.…”
Section: Catalysis In Stereoselective Mcrsmentioning
confidence: 99%